Brain network dynamics during working memory are modulated by dopamine and diminished in schizophrenia - Braun, Urs; Buhl, Anais; Pergola, Giulio; Menara, Tommaso; Schäfer, Axel; Betzel, Richard F.; Zang, Zhenxiang; Schweiger, Janina I.; Zhang, Xiaolong; Schwarz, Kristina; Chen, Junfang; Blasi, Giuseppe; et al. (Nature Communications, 2021)
Dynamical brain state transitions are critical for flexible working memory but the network mechanisms are incompletely understood. Here, we show that working memory performance entails brain-wide switching between activity states using a combination of functional magnetic resonance imaging in healthy controls and individuals with schizophrenia, pharmacological fMRI, genetic analyses and network control theory. The stability of states relates to dopamine D1 receptor gene expression while state transitions are influenced by D2 receptor expression and pharmacological modulation. Individuals with schizophrenia show altered network control properties, including a more diverse energy landscape and decreased stability of working memory representations. Our results demonstrate the relevance of dopamine signaling for the steering of whole-brain network dynamics during working memory and link these processes to schizophrenia pathophysiology.